Crystal-to-crystal transformation amongst dimorphs of racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates that achieves halogen bonding contacts - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2008)
{Racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (1) and chloro (2)) produced two polymorphs each, thin needle type crystals (Form I) were obtained from methanol, whereas larger rectangular crystals (Form II) were produced from ethyl acetate. Both forms could be produced concomitantly on crystallization (of 1 or 2) from ethyl acetate-light petroleum ether mixture; the yield of Form II crystal was always much more compared to Form I crystals. Although, a one-dimensional isostucturality linking molecules via O-H center dot center dot center dot O hydrogen bonding is seen in both forms, the difference arises in linking these chains. In larger Form II crystals (of 1 and 2), the adhesions are via halogen bonding (C-X center dot center dot center dot O=C

Crystal-to-crystal thermal phase transition amongst dimorphs of hexa-O-p-toluoyl-myo-inositol conserving two-dimensional isostructurality - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystengcomm, 2010)
Triclinic (P-1) crystals of hexa-O-p-toluoyl-myo-inositol obtained from common organic solvents exhibited single crystal-to-single crystal irreversible phase transition centered at similar to 250 degrees C. The transformation of these crystals to monoclinic P2(1)/n form was revealed using DSC and X-ray diffraction studies. The latter crystals could also be produced by melt crystallization. Crystal structure analysis revealed that the molecules in both forms are linked via bifurcated C-H center dot center dot center dot O interactions to make almost identical centrosymmetric dimers. The neighbouring dimers are bridged via C-H center dot center dot center dot O and aromatic pi center dot center dot center dot pi stacking interactions to create two-dimensional isostructural assemblies. The difference in the two crystal forms arises from linking of the centrosymmetric dimers along the third dimension; the dimers are centrosymmetrically bridged in the triclinic form, while they have n-glide relationship in the monoclinic form. Comparison of the dimorph structures further revealed that they are actually an excellent case of morphotropism since dimorphs are related by non crystallographic rotation and translation of their basic motif (centrosymmetric dimers) that transforms the triclinic (P-1) phase to a monoclinic (P2(1)/n) phase.

Comparison of racemic epi-inosose and (-)-epi-inosose - Krishnaswamy, Shobhana; Patil, Madhuri T.; Shashidhar, Mysore S. (ACTA Crystallographica Section C-Crystal Structure Communications, 2011)
The conversion of myo-inositol to epi-inositol can be achieved by the hydride reduction of an intermediate epi-inosose derived from myo-inositol. (-)-epi-Inosose, (I), crystallized in the monoclinic space group P2(1), with two independent molecules in the asymmetric unit [Hosomi et al. (2000). Acta Cryst. C56, e584-e585]. On the other hand, (2RS,3SR,5SR,6SR)epi-inosose, C6H10O6, (II), crystallized in the orthorhombic space group Pca2(1). Interestingly, the conformation of the molecules in the two structures is nearly the same, the only difference being the orientation of the C-3 and C-4 hydroxy H atoms. As a result, the molecular organization achieved mainly through strong O-H center dot center dot center dot O hydrogen bonding in the racemic and homochiral lattices is similar. The compound also follows Wallach's rule, in that the racemic crystals are denser than the optically active form.

Chiral crystals from an achiral molecule: 4,6-di-O-benzyl-1,3-O-benzylidene-2-O-(4-methoxybenzyl)-myo-5-inosose - Gurale, Bharat P.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
The title achiral compound, C35H34O7, crystallizes in the chiral monoclinic space group P21. The molecules are densely packed to form a helical assembly along the crystallographic twofold screw axis via CH...O and CH...p interactions. Interestingly, the unit-translated helical chains are loosely connected via a rather uncommon edge-to-edge PhH...HPh short contact (H...H = 2.33 angstrom).

Correlation of the solid-state reactivities of racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate and its 4,4 `-bipyridine cocrystal with their crystal structures - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Structural Chemistry, 2014)
Racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate, C21H18O8, (1), shows a very efficient intermolecular benzoyl-group migration reaction in its crystals. However, the presence of 4,4 `-bipyridine molecules in its cocrystal, C21H18O8 center dot C10H8N2, (1)center dot BP, inhibits the intermolecular benzoyl-group transfer reaction. In (1), molecules are assembled around the crystallographic twofold screw axis (b axis) to form a helical self-assembly through conventional O-H center dot center dot center dot O hydrogen-bonding interactions. This helical association places the reactive C6-O-benzoyl group (electrophile, El) and the C4-hydroxy group (nucleophile, Nu) in proximity, with a preorganized El center dot center dot center dot Nu geometry favourable for the acyl transfer reaction. In the cocrystal (1)center dot BP, the dibenzoate and bipyridine molecules are arranged alternately through OH center dot center dot center dot N interactions. The presence of the bipyridine molecules perturbs the regular helical assembly of the dibenzoate molecules and thus restricts the solid-state reactivity. Hence, unlike the parent dibenzoate crystals, the cocrystals do not exhibit benzoyl-transfer reactions. This approach is useful for increasing the stability of small molecules in the crystalline state and could find application in the design of functional solids.
Keywords: acyl transfer; cocrystal; crystal structure; design of functional solids; helical assembly; hydrogen bonding; myo-inositol; solid-state reactions

Crystal-to-crystal thermal phase transformation of polymorphs of isomeric 2,3-naphthalene diol ditoluates: mechanism and implications for molecular crystal formation and melting - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2014)
Isomeric para- (1) and meta- (2) ditoluate derivatives of naphthalene 2,3-diol exhibited polymorphism producing three (Forms 1I, 1II, 1III) and two (Forms 2I, 2II) polymorphs each, respectively, depending on the solvent and conditions of crystallization. Crystal forms 1I, 1II, and 2I could be obtained repeatedly, whereas crystal forms 1III and 2II were obtained (separately) in one of the crystallization experiments, each. All the crystal forms were stable at ambient conditions, except for Form 2II, which disintegrated to a powder over 45 days. In contrast, the ortho-ditoluate (3) of naphthalene 2,3-diol did not exhibit polymorphism; it yielded fibrous chiral crystals from different solvents/conditions. Crystal structure analysis of all these polymorphs revealed dominance of energetically similar weak intermolecular interactions such as CH center dot center dot center dot O, CH center dot center dot center dot pi, pi center dot center dot center dot pi, and their interplay in molecular aggregation resulting in polymorphic modifications. Differential scanning calorimetry (DSC), hot stage microscopy, single crystal and powder X-ray diffraction measurements revealed crystal-to-crystal thermal transformation of Forms 1I and 1II crystals to Form 1III crystals and Form 2II crystals to Form 2I crystals. The transformation of Form 1I and Form 1II crystals to Form 1III crystals can be viewed as progressive destabilization of the crystal lattice during heating and converting to metastable phase, whereas the conversion of Form 2II to Form 2I crystals can be considered as reorganization of an unstable crystalline phase to a stable crystalline phase. Hence comparative studies of the structure of stable, metastable, or transient crystals and crystal-to-crystal transformations involving these forms could aid in unraveling the process of crystallization.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2015)
2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through OH...O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of p-ditoluate through C-H...pi interactions. In 1:1 cocrystals of the m-ditoluate, naphthalene diol molecules generate a zigzag pattern through O-H...O hydrogen bonding interaction involving -OH of the diol and the C=O of the m-ditoluate. Intermolecular toluoyl group transfer reaction was more facile in cocrystals of the p-ditoluate as compared to cocrystals of the m-ditoluate. This difference in reactivity is consistent with the relative geometry of the electrophile (El, C-O) and the nucleophile (Nu, OH) in these cocrystals. A comparison of the cocrystallization behavior and structure of the two cocrystals with their constituents suggests that the position of the methyl group is crucial for cocrystal formation. A survey of the CSD revealed that the incidence of polymorphism and cocrystals formation decreases (number of hits) in the order para- > ortho- > meta- for disubstituted benzene derivatives. This suggests that compounds prone to exhibit polymorphism have more propensities to form cocrystals as compared to those that resist polymorphism. This information could be useful while selecting cocrystal formers and construction of supramolecular functional assemblies with desired properties.

Clues from crystal structures pave the way to access chiral myo-inositol derived versatile synthons: resolution of racemic 4-o-allyl-myo-inositol-1,3,5-orthoesters via corresponding dicamphanates by crystallization - Patil, Nivedita T.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Racemic 4-O-allyl-myo-inositol-1,3,5-orthoesters were resolved as the corresponding diastereomeric dicamphanates by crystallization from alcoholic solvents. Crystals of the two diastereomers of myo-inositol orthoacetate and one diastereomer each of myo-inositol orthoformate and myo-inositol orthobenzoate were obtained in >99% purity, on gram scale. The configuration of all these diastereomers was established by conversion to known chiral myo-inositol derivatives as well as by single crystal structure analysis. It is interesting to note that the procedures for the separation of diastereomeric myo-inositol orthoesters could be evolved due to the knowledge of crystal growth and crystal structures of inositol derivatives of comparable molecular structures. Due to the synthetic versatility of myo-inositol orthoesters, the methods described provide rapid and convenient access to a variety of chiral inositol derivatives with high synthetic potential.

Correlation of intermolecular acyl transfer reactivity with noncovalent lattice interactions in molecular crystals: toward prediction of reactivity of organic molecules in the solid state - Krishnaswamy, Shobhana; Shashidhar, Mysore S. (Journal of Organic Chemistry, 2018)
Intermolecular acyl transfer reactivity in several molecular Acyl transfer reactivity can be predicted in solution based crystals was studied, and the outcome of the reactivity was analyzed in the light of structural information obtained from the crystals of the reactants. in solid state Minor changes in the molecular structure resulted in significant variations in the noncovalent interactions and packing of molecules in the crystal lattice, which drastically affected the facility of the intermolecular acyl transfer reactivity in these crystals. Analysis of the reactivity vs crystal structure data revealed dependence of the reactivity on electrophile ... nucleophile interactions and C-H center dot center dot center dot pi interactions between the reacting molecules. The presence of these noncovalent interactions augmented the acyl transfer reactivity, while their absence hindered the reactivity of the molecules in the crystal. The validity of these correlations allows the prediction of intermolecular acyl transfer reactivity in crystals and co-crystals of unknown reactivity. This crystal structure-reactivity correlation parallels the molecular structure-reactivity correlation in solution-state reactions, widely accepted as organic functional group transformations, and sets the stage for the development of a similar approach for reactions in the solid state.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity (vol 15, pg 12 - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2019)

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction